Topological One-Way Edge States in an Air-Hole Honeycomb Gyromagnetic Photonic Crystal - Peng, Chaoqun; Chen, Jianfeng; Qin, Qiumeng; Li, Zhi-Yuan (Frontiers in Physics, 2022)
Topological one-way edge states have attracted increasing attention because of their intriguing fundamental physics and potential applications, particularly in the realm of photonics. In this paper, we present a theoretical and numerical demonstration of topological one-way edge states in an air-hole honeycomb gyromagnetic photonic crystal biased by an external magnetic field. Localized horizontally to the edge and confined in vertical direction by two parallel metallic plates, these unique states possess robust one-way propagation characteristics. They are strongly robust against various types of defects, imperfections and sharp corners on the path, and even can unidirectionally transport along the irregular edges of arbitrary geometries. We further utilize the one-way property of edge states to overcome entirely the issue of back-reflections and show the design of topological leaky wave antennas. Our results open a new door towards the observation of nontrivial edge states in air-hole topological photonic crystal systems, and offer useful prototype of robust topological photonic devices, such as geometry-independent topological energy flux loops and topological leaky wave antennas.